Keragaman Hama dan Musuh Alami pada Pertanaman Padi (Oryza sativa) di Wawotobi, Sulawesi Tenggara - Sari, Anella Retna Kumala; Rahmawati, Dian; Samrin, Samrin (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2020)
Obtaining an optimum high yield of rice is confronted by pests that disrupt the productivity. Pest control by applying chemical pesticide is dangerous for the natural enemies therefore, it is necessary to introduce an integrated pest management, based on the natural enemies conservation in the field. Research was conducted in Wawotobi, Konawe Regency, Southeast Sulawesi from Februari to Juni 2019, aimed to understand the diversity of pests and natural enemies in rice crop, particularly arthropods group. The information is useful as a resource base in the implementation of an integrated pest management on rice agroecosystem. Pest observation was done by catching the insects using sweep net and were directly counted at the location. Diversity index of pest was analyzed using Shannor-Weinner equation and insect dominance using Simpson Index of Dominance equation. The utilization of improved rice varieties greatly affected the population of pests and natural enemies. Total of 7 species of pest arthropods and 6 species of natural enemy arthropods were identified at the experimental location. Therefore, the population of pests and natural enemy arthropods were considered at balance. The most dominance pest arthropods was brown planthopper, particularly on Tarabas variety and spider was the most dominant natural enemy.Â